No room to live: urban overcrowding in Edwardian Britain - Ian Gazeley; Andrew Newell (Institute for the Study of Labor (IZA), 2009)
We study the extent of overcrowding amongst British urban working families in the early 1900s and find major regional differences. In particular, a much greater proportion of households in urban Scotland were overcrowded than in the rest of Britain and Ireland. We investigate the causes of this spatial distribution of overcrowding and find that prices, especially rents and wages are the proximate causes of the phenomenon. In large cities, ports and cities specialising in old heavy industries high rent and overcrowding are more prevalent. Within cities, but not between cities, variations in infant mortality are clearly correlated with measures of overcrowding. All the findings are consistent with a core-periphery view of urban households choosing the location and size of housing to balance the health risks of overcrowding against the risks associated with lower and less regular incomes in places where rents are lower.
urn:nbn:de:101:1-2009061940
Keywords: I10; N33; R12; 330; Poverty; rent; overcrowding; Scotland; 1904; infant mortality; Bowley; Städtische Armut; Städtische Bevölkerungsentwicklung; Städtische Wohnungsversorgung; Miete; Kindersterblichkeit; Regionale Disparität; Großbritannien; Schottland